Stock assessment of sciaenid resources of India - Rao, T Appa; Mohan, R S Lal; Chakraborty, S K; Murty, V Sriramachandra; Nair, K V Somasekharan; Vivekanandan, E; Raje, S G (Indian Journal of Fisheries, 2011)
The catches of Jew fishes decreased from 1979 10 1980 and later increased in stages fwm 1981 to1984, 1985 to 87 and 1988 to 89. Gujarat and Maharashtnl together contributed 52% oftota! sciacoid catchesalong the west coast. In both the statf"-s. the landings during the first few years showed an increasing trendwhereas during the remaining period, the catches and percentage contributioo varied. Along the east coastalso the sciaenid landings showed annual fluctuations. Aloog the west coast. O/oli/nus cuyi",i, Johnuopsrr.acmrhYflus. ProlOfliiJea diacanlhus, Johnieops vogleri. Johnius glaucus and JO/"Jlieops 3ina dominatedwhcr"", s along the east coaSI Johnius ClJruJlI:J, i’en.nahia macrophlhafmus, Kalh.Jia axiiiaris, Johnuopsvogl"rj and JohnillS dliSsumieTi were the dominant species. The seasonal abundance of sciaenids varied indiffc!l’!nt stales at diff::renl times. Sciallllids are carnivorous feeding on teleos!eans and crustaceans.Spawniug season of each spedes ... aried from place to place. Other biological aspects like size at firstma!llrity, fecundity, seA ratio, lengm-wei&hJ. relationship, age and growth, etc for the common species werealso studied. Estimations were made on the yield and biomass at various ievels of fishin!: effort for importantspecies of sciacnids.